Membrane physiology of retinal glial (Muller) cells - Newman, EA (J Neurosci, 1985)
Electrophysiological techniques were used to determine the ion selectivity properties and the spatial distribution of the membrane conductance of amphibian Muller cells. Membrane potential changes recorded during ion substitution experiments in frog (Rana pipiens) retinal slices demonstrated that the Muller cell K+:Na+ membrane permeability ratio is approximately 490:1 and that cell Cl- permeability is extremely low. In frog retinal slices, Muller cell input resistance was 8.5 megohms when measured in the inner plexiform layer and 4.8 megohms when measured in the optic fiber layer. Intact, enzymatically dissociated salamander (Ambystoma tigrinum) cells had an input resistance of 7.9 megohms, whereas cells lacking their endfoot process (removed by surgical microdissection or by shearing force) had a resistance of 152 megohms. Pressure ejection of a 100 mM K+ solution near the proximal surface of the endfeet of dissociated salamander cells produced depolarizations 7 times greater than did ejections near the lateral face of the endfoot and 24 to 50 times greater than did ejections near other cell regions. Similar K+ ejection results were obtained from Muller cells in salamander and frog retinal slices. Taken together, these results demonstrate that in both the frog and the salamander, approximately 95% of the total membrane conductance of Muller cells is localized in the cell's endfoot process. In salamander, the specific membrane resistance of the endfoot membrane was estimated to be 32 ohm X cm2 whereas the specific resistance of the remainder of the cell was 7300 ohm X cm2. This remarkably nonuniform conductance distribution has important consequences for theories concerning K+ regulation in the retina and for mechanisms underlying electroretinogram generation.